Video Pembelajaran Bernuansa Problem Based Learning dengan Muatan IPS Kelas IV Sekolah Dasar - Ida Bagus Kade Raka Adnyana (Jurnal Ilmiah Pendidikan Profesi Guru, 2021)
This research is motivated by the problems that exist in the field regarding the difficulties of teachers in finding learning media that can be used in online learning. The purpose of this study was to produce a learning video with the nuances of Problem Based Learning for social studies content for grade IV elementary schools. This research is development research with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). Data collection methods used in this study were interviews, document recording, and questionnaires. In this study, the learning video design test was carried out by several experts and students which included (1) learning material experts, (2) learning design experts, (3) learning media experts, too (4) individual trials. The analysis used is descriptive quantitative and qualitative data analysis. The results showed that the validity by experts, the percentage level of feasibility of learning videos based on material experts was 93.75% with very good qualifications. The percentage level of feasibility according to learning design experts is 90.38%. The percentage rate of eligibility according to media experts is 90.62%. The percentage level of eligibility for learning videos according to individual trials is 92.42% with very good qualifications. Based on the results of the study, it can be concluded that the learning video with the nuances of Problem Based Learning is feasible to be used in the learning process on the content of social studies class IV elementary school.